The Fairness of Price and Satisfaction On Loyalty Of Digital Streaming Services Users - Harmawan, Wisnu Agus; Situmorang, Syafrizal Helmi; Rini, Endang Sulistya (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
The digital streaming industry faces increasing competition, particularly in price competition. The subscription prices of digital streaming platforms vary, making it difficult for companies to maintain price fairness. The fairness of price is a psychological factor that impacts consumer reactions to prices, and it significantly impacts satisfaction and loyalty. This study examines the relationship between price fairness, consumer satisfaction, and loyalty among digital streaming subscribers in Medan City. The sample consisted of 180 respondents, with the data collected using a questionnaire. The results showed that the fairness of price has a positive and significant impact on the satisfaction of customers and loyalty, the satisfaction of consumers positively and significantly affects loyalty, and price fairness influence consumer loyalty through the satisfaction of customers positively and significantly. The study suggests that digital streaming companies should adjust prices to meet consumer satisfaction and loyalty. Future research should explore engagement and expand the types of streaming platforms to gain further understanding. The findings can help digital streaming companies adjust prices to meet customer needs and preferences, ultimately increasing consumer satisfaction and loyalty.